Strength Assessment of Stiffened-Panel Structures against Buckling Loads: FE Benchmarking and Analysis - M. Sholikhah; R. Ridwan; A. R. Prabowo; T. Ghanbari-Ghazijahani; I. Yaningsih; N. Muhayat; D. D. D. P. Tjahjana; R. Adiputra; J. M. Sohn (Civil Engineering Journal, 2024)
This research endeavors to examine the effect of stiffener shapes on the structural capacity of stiffened-plate structures, specifically focusing on Tee (T), Angle (L), and Flat (I) stiffened plates. The primary objectives are threefold: firstly, to quantify the critical load values during the buckling phenomenon for T, L, and I stiffened plates; secondly, to assess model deformation upon failure; and thirdly, to investigate whether the buckling behavior of T, L, and I stiffened plates correlates with distinct failure patterns. Employing numerical simulation through the finite element method, this study sheds light on previously unexplored aspects of structural behavior. The findings indicate that angle stiffeners exhibit superior load-bearing performance compared to flat bars. Notably, the research reveals a substantial increase in maximum compressive load by at least 15.90% with Tee bar and 8.25% with angle bar stiffeners when the stiffened panels undergo a 5 mm displacement, presenting a potential avenue for structural enhancement. Additionally, the study demonstrates that T bars outperform in terms of resisting buckling. Noteworthy is the novel approach of examining the combined effect of transverse frame, longitudinal frame, and hull girder under buckling scenarios, a facet not explored in previous research. Furthermore, the utilization of steel S355JR-EN10210 as a material introduces a unique dimension not previously considered in these scenarios. Doi: 10.28991/CEJ-2024-010-04-03 Full Text: PDF